Investigation on hydrogen evolution reaction performance of porous electrode prepared by laser powder bed fusion. (February 2022) - Cai, H.Y.; Ma, J.F.; Li, N.N.; Li, W.P.; Li, S.P.; Qiu, M.X.; An, H.Y.; Zhang, S.W.; Li, X.Q.; Chen, J.R.; Lin, S.H.; Xu, J.B.; et al.
Abstract: The additive manufacturing (AM) process attracts widespread attention because it generates devices with of highly complex and precise 3D geometries that are difficult to realize using traditional fabrication methods. In this study, two kinds of porous cylindrical electrodes with different lattice structures are prepared by laser powder bed fusion (L-PBF). The influence of electrode lattice structure parameters (structure type, lattice unit size) on the efficiency of hydrogen evolution reaction (HER) is investigated. The HER efficiency of the electrode is evaluated through the energy consumption experiment and the electrochemical analysis. The results reveal that the porous electrode has significantly larger physical specific surface area and lighter weight than the solid cylindrical electrode, the electrode with the Dode Medium structure has better hydrogen evolution performance than the Rhombic Dodecahedron lattice structure under the same lattice unit size; in both structures, the electrode with 8 mm lattice aperture has better electrolytic water activity to produce hydrogen. The present work shows that AM technology can provide a flexible processing solution for high specific surface area electrodes required for large-scale and efficient industrial hydrogen production. Highlights: Electrodes with lattice structures were prepared by the laser powder bed fusion. The structure of electrode increased its specific surface area and lightweighting. The hydrogen evolution reaction efficiency is influenced by lattice structure. AM technology provides a solution for electrode forming required for industrial.